Enhancing Critical Thinking Skills through Group Investigating Models and “Datar” “Pakar” Media for Facing the 21st Century - Utaminingsih, Esty Setyo; Irchamni, Achmad; Utami, Yeri; Shabrina, Monita Nur (Universitas Negeri Semarang, 2024)
The critical thinking skills of fourth-grade elementary school students have been found to be lacking, hindering their ability to effectively process information. This research aims to explore the impact of group investigation learning models supported by “Datar” and “Pakar” media on enhancing critical thinking skills in social science education. Employing an experimental